Desenvolvimento de método para hidrólise de aminoácidos totais por equipamento de micro-ondas - Alves, Priscilla Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
O presente trabalho descreve o projeto desenvolvido durante o período de estágio supervisionado obrigatório para conclusão de graduação em Bacharelado em Química Ambiental Tecnológica, oferecido pela Universidade Estadual Paulista “Júlio de Mesquita Filho”, campus Bauru. O mesmo foi realizado em uma empresa do ramo alimentício que promove saúde e bem-estar para seres humanos e nutrição animal através de processos biotecnológicos. Visando o desenvolvimento de alimentos, é de extrema importância que todos os produtos tenham seu perfil de nutrientes orgânicos bem definidos, bem como o perfil aminoacidico, que é traçado através da análise de aminoácidos livres e totais; em seu método tradicional o mesmo é realizado através da hidrólise ácida em bateria de extração e posterior análise por cromatografia líquida de alta eficiência (HPLC-DAD). Entretanto, o método tradicional apresenta alguns pontos que apresentaram potencial de melhoria. Sendo assim, as atividades realizadas consistem no desenvolvimento de um método para hidrólise de aminoácidos totais por micro-ondas, visando otimizar o método original, reduzindo o tempo necessário para análise, redução de competição com outros ensaios e conservação externa do equipamento.

The present work describes the project developed during the mandatory supervised internship period for completion of the Bachelor's Degree in Technological Environmental Chemistry, offered by the Universidade Estadual Paulista “Júlio de Mesquita Filho”, Bauru campus. The same was done in a food company that promotes health and well-being for humans and animal nutrition through biotechnological processes. Aiming at food development, it is extremely important that all products have their organic nutrient profile well defined, as well as the amino acid profile, which is traced through the analysis of free and total amino acids; in its traditional method, the same is carried out through acid hydrolysis in an extraction battery and subsequent analysis by high performance liquid chromatography (HPLC-DAD). However, the traditional method has someThe present work describes the project developed during the mandatory supervised internship period for completion of the Bachelor's Degree in Technological Environmental Chemistry, offered by the Universidade Estadual Paulista “Júlio de Mesquita Filho”, Bauru campus. The same was done in a food company that promotes health and well-being for humans and animal nutrition through biotechnological processes. Aiming at food development, it is extremely important that all products have their organic nutrient profile well defined, as well as the amino acid profile, which is traced through the analysis of free and total amino acids; in its traditional method, the same is carried out through acid hydrolysis in an extraction battery and subsequent analysis by high performance liquid chromatography (HPLC-DAD). However, the traditional method has some points that have potential for improvement. Therefore, the activities carried out consist of the development of a method for hydrolysis of total amino acids by microwave, aiming to optimize the original method, reducing the time required for analysis, reducing competition with other tests and external conservation of the equipment. points that have potential for improvement. Therefore, the activities carried out consist of the development of a method for hydrolysis of total amino acids by microwave, aiming to optimize the original method, reducing the time required for analysis, reducing competition with other tests and external conservation of the equipment.
Development of a method for hydrolysis of total amino acids by microwave equipment
Keywords: Levedura; Aminoácidos; Hidrólise; Cromatografia; Yeasts; Amino acids; Hydrolysis; Chromatography